DAMPAK PARTISIPASI DAN MOTIVASI TERHADAP KESEHATAN MENTAL PESERTA PELATIHAN SANTRI SIAP GUNA - Fahmi, Rahmat; Ramadani, Rika Fitri; Maka Raja, Faisal Hamid; ., Sardin; ., Aminah (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2025)
Mental health issues, particularly anxiety and stress, have become a concern in Indonesia, especially among young people. The Indonesian Ministry of Health (2020) reported that 18.1% of the population experienced emotional disorders, with anxiety and stress being the most common problems. These conditions are often triggered by social, economic and academic pressures, significantly affecting individual well-being. This study investigated the effect of active participation and intrinsic motivation in the Santri Siap Guna (SSG) Training program Daurut Tauhiid Bandung, a spiritual and character-building initiative, on participants' mental health. Using a sample of 30 participants, this study employed multiple regression analysis to assess the relationship between these variables and the reduction of anxiety, stress, and increased mental resilience. The results showed that active participation and intrinsic motivation significantly contributed to improved mental health, providing valuable insights for developing character and spirituality-based education programs aimed at strengthening mental health, particularly for Indonesian youth.